Fresh and Dried Fish Consumption and its Contributory Factors: A Study of Malappuram, Kerala - M. V. Sajeev; A. K. Mohanty, C. G. Joshy, R. Gopika, P. K. Abdul Jabbar, Suseela Mathew, C. N. Ravishankar (Indian Journal of Extension Education, 2022)
The study investigates fresh and dried fish consumption patterns and factors determining fish purchase among the people of Malappuram district, Kerala. 200 fish consumer households belonging to varied socio-economic backgrounds were surveyed using a structured questionnaire. Garret ranking identified ‘convenience perception’ (14.92), ‘provision of home delivery’ (8.62), ‘availability of dressing facility’ (8.61), ‘sensory perception’ (7.75) and ‘information on fish sold in market’ (7.26) as the most important factors influencing fish purchase among the households. The factors identified will guide in preparation of strategies for modern fish business aiding the emerging digital fish market ecosystem in our country. The per capita fish consumption estimated at 2.6 kg/person/month is far higher than the national average. Sardine and mackerel were the two most important species preferred by the respondents. Majority of the families were found to consume dried fishes 1-2 times a week. The study indicated a healthy level of per capita fresh fish consumption while further efforts can be made to improve the dried fish consumption among the households. The results will aid policy makers in designing strategies aimed at bringing fish consumption to recommended dietary intake levels in poorly faring states and territories of the country.